"Capillary Permeability" in Patients with Collagen Vascular Diseases. Issue 5803 (25th March 1972) - Marks, Janet; Birkett, D. A.; Shuster, Sam
Abstract : "Capillary permeability" to serum albumin has been measured in patients with collagen vascular diseases by a method which compares the dilution of intravenously injected 131 I-human serum albumin and 51 Cr-R.B.C.s. The results indicate an increased capillary permeability comparable to that which occurs in patients with extensive inflammatory skin disease. We suggest that this increased capillary permeability may be the cause of the episodes of oedema which occur in patients with collagen vascular diseases such as disseminated lupus erythematosus, systemic sclerosis, dermatomyositis, polyarteritis nodosa, and rheumatoid arthritis. "Spontaneous periodic oedema" may be the presenting feature of collagen vascular disease and is due to increased capillary permeability.